The Bobbed Haired Bandit : a True Story of Crime and Celebrity in 1920s New York. - Duncombe, Stephen (NYU Press, 2006)
Ripped straight from the headlines of the Jazz Age, The Bobbed Haired Bandit is a tale of flappers and fast cars, of sex and morality. In the spring of 1924, a poor, 19-year-old laundress from Brooklyn robbed a string of New York grocery stores with a "baby automatic," a fur coat, and a fashionable bobbed hairdo. Celia Cooney's crimes made national news, with the likes of Ring Lardner and Walter Lippman writing about her exploits for enthralled readers. The Bobbed Haired Bandit brings to life a world of great wealth and poverty, of Prohibition and class conflict. With her husband Ed at her sid